Leipziger Demontagebuch: Demo, Montag, Tagebuch, Demontage - Schneider, Wolfgang; Förster, Peter; Agsten, Dagmar (Kiepenheuer, 1990)
Wolfgang Schneider (Hrsg.): "Leipziger Demontagebuch". Gustav Kiepenheuer Verlag, Leipzig und Weimar 1990. 182 S., geb., 29,80 DM